Writing Narrative Texts Through Genre-Based Pedagogy Using Facebook among the Suku Anak Dalam in Jambi - Wahyuni, Rizki Niko; Rustam, Rustam; Priyanto, Priyanto (LP. Ma'arif Janggan Magetan, 2026)
Narrative writing is not merely a linguistic skill but a medium for preserving cultural memory, expressing identity, and transmitting indigenous knowledge across generations. This study aims to examine the implementation of genre-based pedagogy mediated through Facebook in teaching narrative writing among the Suku Anak Dalam (SAD), an indigenous community in Jambi, Indonesia, and to explore its linguistic and socio-cultural impacts. Employing a qualitative case study design grounded in ethnopedology, the research involved eight indigenous learners, two facilitators, and one cultural leader. Data were collected through participatory observation, in-depth interviews, analysis of students’ narrative texts, and digital interactions within a Facebook learning group. The findings show that the three stages of genre pedagogy—modeling, joint construction, and independent construction—supported learners’ development of narrative structure, coherence, cultural representation, and reflective meaning-making. While challenges in writing mechanics, such as grammar and punctuation, remained, learners demonstrated meaningful progress in transforming oral storytelling traditions into cohesive written narratives. Beyond linguistic outcomes, the learning process fostered increased motivation, confidence, and cultural pride, and preserved indigenous stories through digital documentation. The study concludes that integrating genre based pedagogy with social media can effectively bridge oral traditions and digital literacy, positioning writing as a form of cultural empowerment for indigenous and marginalized communities.